Macroeconomics - L. Slavin Stephen (American : Mc Graw-Hill, 2007)
Steve Slavin’s lively and comprehensive Macroeconomics has a student-friendly, step-by-step approach; value pricing; and a built-in Workbook/Study Guide. Instructors and students like the author’s humorous anecdotes, direct language, and easy conversational style. The text encourages active rather than passive reading.
Keywords: Macroeconomics